(untitled) (Orinoquia, 2021)
320 black women from the cities of Cartagena, Montería and Apartadó became leaders and educators in the environment of the “Actúa con Corazón de Mujer” program of the Colombian Society of Cardiology and the Colombian Heart Foundation after receiving a training program with the proposal of care as a lifestyle. Twelve face-to-face sessions of the facilitating team of the Colombian Heart Foundation made it possible to fulfill the training objective. 320 women were trained with 141 in Apartadó, 109 in Cartagena and 70 in Montería with 12 face-to-face sessions in 6 months. The educational intervention aimed to guarantee an impact on public health in the short, medium and long term, by sensitizing 320 women to act with the heart of a woman and to adopt in their daily life the "Method 10 of care" as a style of life, which encourages new healthy behaviors with the consequence of lowering the levels of predisposition to develop diseases associated with lifestyles and learning to control diseases or risk factors already installed, through the adoption of lifestyles that guarantee care. A change in the perception of health was evidenced in 80% of the participants, of which and at least 50% presented decreases in anthropometric measurements. The most significant changes were in body weight and waist circumference. Direct population interventions must become public policies that guarantee access to knowledge to educate less favored populations in health. The absence of education in health and lifestyles is the most significant determinant to achieve the preservation of health. Review the intervention in flipbook “ACTÚA CON CORAZON DE MUJER” Review the intervention on the website “ACTÚA CON CORAZON DE MUJER